2019
DOI: 10.4067/s0718-27242019000100053
|View full text |Cite
|
Sign up to set email alerts
|

Defense System, Industry and Academy: The Conceptual Model of Innovation of the Brazilian Army

Abstract: This article intends to identify the technological parks existing in the headquarters of military regions of the Brazilian Army, with the premise that these habitats are capable of forming nuclei of governance of technological innovation. The problem is that since the year of 2016, the Brazilian Army created the Defense, Industry and Academy System (SisDIA) of Innovation, a conceptual model of the Triple-Helix, aiming to promote the development of innovations taking advantage of the Army presence in all region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
1
5
0
1
Order By: Relevance
“…Relating our results to the results of earlier research in the same geographic region, the article by Simões et al [2] also identified a relationship between UIG, leading to a TH approach. Similar results were identified in the Brazilian Army, which in 2016 created the defense, industry and academy system (SisDIA) of innovation, operating in a TH model, to promote the development of innovations by taking advantage of the presence of the army in all regions of the country [67]. In Portugal, due to DTIB's segmentation, the UIG is managed in consortia supported by the government.…”
Section: Empirical Model For the Defense Industrysupporting
confidence: 54%
“…Relating our results to the results of earlier research in the same geographic region, the article by Simões et al [2] also identified a relationship between UIG, leading to a TH approach. Similar results were identified in the Brazilian Army, which in 2016 created the defense, industry and academy system (SisDIA) of innovation, operating in a TH model, to promote the development of innovations by taking advantage of the presence of the army in all regions of the country [67]. In Portugal, due to DTIB's segmentation, the UIG is managed in consortia supported by the government.…”
Section: Empirical Model For the Defense Industrysupporting
confidence: 54%
“…The topics responsible for the growing number of publications since 2018 are mainly related to defence innovation and technology transfer of the Spanish defence industry (Briones-Peñalver et al 2020;Oliva et al 2019;Callado-Muñoz et al 2020), the expansion of the Chinese Defence industry (Béraud-Sudreau and Nouwens 2021; Dominese 2020), and the Brazilian R&D projects (Bernat and Karabag 2018;Silva and Olavo-Quandt 2019;Fernandes et al 2020). The most notable investment in research refers to the Spanish defence industry, which is also shown in Figure 3 (top 3 countries).…”
Section: Findings From the Slrmentioning
confidence: 99%
“…A successful example of the interaction in ecosystems for the defense sector is Route 128 in Massachusetts, USA, which aggregates technological interests, high skilled human resources, infrastructure and the existence of venture capital in the region through the government, industries and academia (Massachusetts Institute of Technology and Harvard University) (Silva & Quandt, 2019).…”
Section: Theoretical Framework 21 Organizational Innovation Processmentioning
confidence: 99%
“…While previous research on R&D investments in the Brazilian defense sector focused on innovation policies (Leske, 2018) and impacts of innovation governance on the regional development of science parks (Silva & Quandt, 2019;Silva, Sá, & Spinosa, 2019), current research still does not present the phases of the innovation processes involved in the sector. In our study, we intend to evaluate the model of the innovation processwhich is promoted by investment policies and present in industrial and academic ecosystemsthrough an applied research that aims to identify the common features among the projects.…”
Section: Introductionmentioning
confidence: 97%